The sympathetic consumer : moral critique in capitalist culture - Skotnicki, Tad (Culture and economic life., 2021)
"When people encounter goods in the marketplace - sugar, clothes, phones, etc. - there is a slim chance they will seek information about the origins of those goods. Far more likely is that the goods will remain anonymous, and the labor that went into making them, the supply chain through which they traveled, will stay mysterious, distant, unacknowledged. In this book, Tad Skotnicki argues that this phenomenon is an endemic feature of capitalist societies"--